Impact of health insurance, ADAP, and income on HIV viral suppression among US women in the Women’s Interagency HIV Study, 2006–2009 - Ludema, Christina (J Acquir Immune Defic Syndr, 2016)
BACKGROUND: Implementation of the Affordable Care Act motivates assessment of health insurance and supplementary programs, such as the AIDS Drug Assistance Program (ADAP) on health outcomes of HIV-infected people in the United States. We assessed the effects of health insurance, ADAP, and income on HIV viral load suppression. METHODS: We utilized existing cohort data from the HIV-infected participants of the Women’s Interagency HIV Study (WIHS). Cox proportional hazards models were used to estimate the time from 2006 to unsuppressed HIV viral load (>200 copies/mL) among those with Medicaid, private, Medicare or other public insurance, and no insurance, stratified by use of ADAP. RESULTS: In 2006, 65% of women had Medicaid, 18% had private insurance, 3% had Medicare or other public insurance, and 14% reported no health insurance. ADAP coverage was reported by 284 women (20%); 56% of uninsured participants reported ADAP coverage. After accounting for study site, age, race, lowest observed CD4, and prior health insurance, the hazard ratio (HR) for unsuppressed viral load among those privately insured without ADAP, compared to those on Medicaid without ADAP (referent group), was 0.61 (95% CI: 0.48–0.77). Among the uninsured, those with ADAP had a lower relative hazard of unsuppressed viral load compared to the referent group (HR, 95% CI: 0.49, 0.28–0.85) than those without ADAP (HR, 95% CI: 1.00, 0.63–1.57). CONCLUSIONS: While women with private insurance are most likely to be virally suppressed, ADAP also contributes to viral load suppression. Continued support of this program may be especially critical for states that have not expanded Medicaid.